Understanding Green Purchase Intention in the Electronic Product Market: The Mediating Role of Green Trust - Bahtiar, Firman Adam; Asih, Daru (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to test and analyze the influence of green perceived value, green awareness, and environmental knowledge on green electronics purchase intention, both directly and through the mediation of green trust. Methodology/approach – A survey that included information on green purchase intention was used to collect data from 200 purchasers and potential purchasers of electronic product in urban cities of Java Island, and a Structural Equation Model (SEM) test was conducted using Smart PLS software. Findings – It was found that green perceived value, green awareness, environmental knowledge, and green trust have a positive and significant influence on green electronic purchase intention. And on the other hand, green trust also has a positive and significant influence in mediating the relationship between green preceived value, green awareness, and environmental knowledge and green electronic purchase intention. Novelty/value – The novelty of this research lies in the integration of the role of Green Trust as a mediator, focusing on the context of the green electronic market in Indonesia, and the use of a comprehensive PLS-SEM analysis method.